Indirect surpassing CO2 utilization in membrane-free CO2 battery. (April 2021) - Kim, Jeongwon; Seong, Arim; Yang, Yejin; Joo, Sangwook; Kim, Changmin; Jeon, Dong Hyup; Dai, Liming; Kim, Guntae
Abstract: Economical and efficient carbon capture, utilization and sequestration technologies are essential for addressing the global challenge to reduce CO2 emissions. However, current CO2 conversion technologies cannot meet the economic and energy requirements due to the sluggish processes for CO2 sequestration. Herein, we rationally designed a membrane-free (MF) Mg-CO2 battery as an advanced approach to sequester CO2 emissions by generating electricity and value-added chemicals without any harmful by-products. The newly-developed MF Mg-CO2 battery operates based on the indirect utilization of CO2 with facile hydrogen generation process, which leads to electrochemical performance of 64.8 mW cm −2 with a high Faraday efficiency (>92.0%). Over the 80 discharge-charge cycles, the outstanding cycling performance with the generation of triple gases, e.g., H2 (g) under discharge and O2 /Cl2 (g) under charge mode, was attained without any degradation. Graphical Abstract: This work presents the membrane-free CO2 battery with indirect utilization of CO2 from organic and hybrid electrolyte metal-CO2 battery. ga1 Highlights: We designed a membrane-free (MF) Mg-CO2 battery as an advanced approach to sequester CO2 emissions by generating value-added chemicals. The newly developed MF Mg-CO2 battery operates based on the indirect utilization of CO2 with facile hydrogen generation process (FE: >92.0 %). The outstanding cycling performance with the generation of triple gases, e.g., H2 (g) under discharge and O2 /Cl2 (g) under charge mode. We have opened the door to electrochemical utilization of CO2 with indirect circulation for future alternative technologies.